Statistical Evaluation of 231 Ears That Received Tympanic Membrane Perforation Closure Using Carbon Dioxide Laser and Collagen Sponge - Kuroda, Kazuhiro; Kuroda, Tatsuaki (International Journal of Practical Otolaryngology, 2024)
The tympanoplasty technique reported by Yuasa et al, wherein autologous tissue is fixed to the perforated tympanic membrane using fibrin glue, is widely used. This technique has also led to the development of several simpler surgical methods using artificial materials not involving the use of fibrin glue. We used a carbon dioxide laser device (OtoLAM, Lumenis Be Japan Inc.) during tympanoplasty to refresh the perforation margin of the tympanic membrane and a collagen sponge with a silicone membrane (Terudermis, Alcare Inc.) as the closure material for tympanoplasty. OtoLAM is used to refresh the perforation margin in a short time. By simply fixing Terudermis to the perforated area using the attached silicone membrane, the surgery can be performed in a short time without the need for autologous tissue collection. For the past 9 years and 5 months, from June 2013 to November 2022, we used this method for tympanic membrane perforation closure in 231 ears. The closure rate after a single operation was not high (78/231; 33.8%) but significantly improved with multiple attempts (161/231; 69.7%). The advantages of this technique are that it is simple, can be performed quickly, is economical as it does not involve the use of fibrin glue, and there is no possibility of blood infection, eliminating the need for a detailed explanation to the patient.
Keywords: tympanoplasty; OtoLAM; Terudermis